Recontextualização do discurso da ciência da linguagem em livros didáticos de língua inglesa - Rossi, Ariane de Fatima Escobar (2012)
In today's technologized and literate society, scientific literacy has been increasingly developing the social function of preparing citizens to act in the most diverse spheres of social life (SANTOS, 2007, p. 480). We understand that scientific literacy refers to the individual‟s capacities of reading, writing, comprehending and expressing points of view (Idem, p. 478), using scientific and technological knowledge in their own life (ULHÔA; GONTIJO; MOURA, 2008, p. 8). Considering the scientific literacy relevance in the current globalized society, the present work has as objective to investigate how the popularization process of language science discourse is constituted in textbooks of English as a foreign language (EFL). We consider science popularization (SP) as the recontextualization of scientific knowledge in the mass media (TV documentary, e-journal, for example) to a non-specialized audience (MYERS, 2003). The corpus of analysis is composed by six sections entitled Reading Beyond the Words from the Prime collection which were selected based on the themes citizenship and human values, according to the Textbooks Guide - TNP 2012 of Modern Foreign Language (BRASIL, 2011). The analysis of the sections is based on guiding questions about some current concepts in the field of EFL: 1) language as genre; 2) reading as critical literacy; and 3) scientific literacy. We adopt Critical Genre Analysis approach (MEURER, 2002; BHATIA, 2004, 2010; MOTTA-ROTH, 2006) which considers the conditions of production, distribution and consumption of texts to the analysis and interpretation of the social practice constituted in a certain genre (MOTTA-ROTH, 2008a, p. 362). The results indicate that there is a perspective of language as discursive genre, for the relation text-context is present in the reading activities. The conception of reading is interactive and critical literacy perpasses some stages of reading, mainly pre-reading and post-reading activities. In relation to the while-reading stage, however the activities give space to critical literacy and interactive reading, they could have a more focused formulation on the relation among text, discursive and social practice. Scientific literacy is also timidly explored, but there is an attempt of defining some concepts of language science by means of resources such as intertextuality and semantic relations, besides activities which explore scientific knowledge when questioning, for example, about the producers, methods and products of science. Generally, there is an attempt of recontextualizing the discourse of language science in the analyzed textbooks. Thus, the language teacher plays the role of agent in the implementation of teaching towards the promotion of scientific literacy in the field of EFL, because language plays the role of mediator in learning other types of knowledge.